Designing ALU using GDI method - Mohammadreza Fadaei (International Journal of Reconfigurable and Embedded Systems (IJRES), 2019)
As CMOS technology is continuously becoming smaller and smaller in nanoscale regimes, and circuit resistance to changes in the process for the design of the circuit is a major obstacle. Storage elements such as memory and flip-flops are particularly vulnerable to the change process. Power consumption is also another challenge in today's Digital IC Design. In modern processors, there are a large number of transistors, more than a billion transistors, which increases the temperature and the breakdown of its performance. Therefore, circuit design with low power consumption is a critical need for integrated circuits today. In this study, we deal with GDI techniques for designing logic and arithmetic circuits. We show that this logic in addition to low power consumption has little complexity so that arithmetic and logic circuits can be implemented with fewer transistors. Various circuits such as adders, differentiation and multiplexers, etc. have been designed and implemented using these techniques, and published in various articles. In this study, we review and evaluate the advantages and disadvantages of these circuits.